The Use of English Children’s Literature to Enrich EFL College Students’ Vocabularies and Reduce Their Reading Anxiety at English Department UNP - Juni Asnita; Leni Marlina (Universitas Negeri Padang, 2022)
This study aims to identify the application of the use of English children's literature, especially short stories to enrich students' vocabulary mastery. The population of this research is EFL College Students in the English department of UNP academic year 2021/2022. Sampling was done by using a random sampling method. The number of samples in this study was 40 students. Data was collected through a questionnaire. This research is descriptive quantitative design research with a quantitative approach. Based on the results of the study, the pre-test value in the K3 class was 553.7 and the post-test value in the K3 class was 583.5. The results of the normality test of the data on the pre-test and post-test for the K3 class were normally distributed with a pre-test sig value of 0.069 and a post-test sig value of 0.078. In class K4 the average score of the students in the pre-test was 566.2 and while the post-test average score for the K4 class was 613.4. The results of the normality test of the data in the pre-test and post-test for class K4 were normally distributed with a pre-test sig value of 0.200 and a post-test sig value of 0.200. The results of the t-test carried out are the value of Sig. (2-tailed) is 0.024 < 0.05, there is a difference in the results of the pre-test and post-test. For the K3 class anxiety reading, the pre-test average score was 85.5 and the post-test average was 91.4. In class K4 for anxiety reading, the pre-test score was 90.5 and the post-test score was 85.5. The results of the pre-test and post-test reading, the value of Sig. (2-tailed) is 0.045 < 0.05. Based on the findings, it can be concluded that the use of English children's literature, especially short stories can be a solution to increasing vocabulary and decreasing reading anxiety for EFL college students' at the English Department of UNP.